The Relationship Between Sports Addiction and Personality Dimensions Based on Cloninger’s Theory in Bodybuilding and Fitness Trainers in Eastern Anatolia Region of Turkey - Cemile Nihal Yurtseven; Mehmet Ilkim; Turhan Toros; Tahir Volkan Aslan; Muzaffer Toprak Keskin; Mehmet Efe; Burhan Başoğlu; Mihriay Musa; Nurgül Özdemir; Serhat Polat; et al. (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Sports addiction, which can significantly impact athletes and coaches, is influenced by various personality traits. This study aims to examine the relationship between sports addiction and personality dimensions according to Cloninger's theory among bodybuilding and fitness trainers in Eastern Anatolia, Turkey. This applied, post-event research involved a statistical population of bodybuilding and fitness trainers in the region, with a sample size of 217 participants selected through stratified random sampling. Data was collected using standardized sports addiction questionnaires and Cloninger's Nature and Character Questionnaire. Statistical analyses, including Pearson correlation, linear regression, independent t-tests, and MANOVA, were conducted using SPSS with a significance level of 0.05. The findings indicate a significant relationship between sports addiction and certain personality dimensions, such as avoidance, dependence on reward, and perseverance. However, novelty was not significantly related to sports addiction. Additionally, significant relationships were found between sports addiction and all character dimensions, including cooperation, self-direction, and self-development. No significant gender differences were observed in sports addiction or between personality dimensions of nature and character among male and female coaches. It is recommended that understanding individuals' personality dimensions can help coaches identify the likelihood of sports addiction symptoms and implement measures to mitigate associated risks.